Time to surgery after radiological diagnosis of brain tumours in Pakistan: A nationwide cross-sectional study - Mohammad Hamza Bajwa; Mashal Murad Shah; Muhammad Usman Khalid; Muhammad Shahzad Shamim; Erum Baig; Naveed Zaman Akhunzada; Altaf Ali Laghari; Muhammad Faraz Raghib; Saad bin Anis; Sameen Siddiqi; Syed Ather Enam (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate waiting times for brain tumour surgery in Pakistan from a nationwide sample and highlight specific affected patient populations. Methods: A nationwide study was conducted as part of the Pakistan Brain Tumour Epidemiology Study; data from 32 high-volume neurosurgical centres were collected. The national sample included 2,750 patients. Time to surgery was calculated by the difference in dates recorded for radiological diagnosis and the date of the first surgery. This was further stratified according to demographic factors, histopathological diagnosis, type of surgical procedure performed and survival outcomes. Results: The data of 1,474 patients for time to surgery was available. Patients travelling to public hospitals had significantly longer mean wait times (94.07 (CI: 85.29, 102.84) vs 75.14 (CI: 54.72, 95.56) days, p<0.001). Significant differences were seen between patients of various age groups, as adolescents (116.63 (CI: 65.27, 167.98) days) and young adults (103.34 (CI: 85.96, 120.72) days) had higher waiting times compared to middle-aged (72.44 (CI: 61.26, 83.61) days) and older (48.58 (CI: 31.17, 65.98) days) adults. No difference was seen between the genders. A significantly longer time to surgery was observed for middle- and lower-socioeconomic class patients. Those undergoing gross total resection of the tumour had significantly (p<0.001) longer waiting times for surgery when compared to STR (sub-total resection), biopsy, and CSF-diversion procedures, for all tumour types. Patients diagnosed with meningioma had the most prolonged waiting periods (106 (CI: 76, 95) days). Gliomas had a mean waiting period of 88 (CI: 73, 103) days across the country. Low-grade gliomas had significantly (p=0.031) longer mean waiting times (99.73 (CI: 61.91, 127.36) days) in comparison to high-grade gliomas (70.13 (CI: 43.39, 89.69 ) days). A significant difference was seen between waiting times for patients who survived surgical procedures for a brain tumour on the most recent follow-up and those who had expired (91.87 (CI: 79, 107.74) vs 77.41 (CI: 59.90, 94.91) days, p<0.001). Conclusion: Prolonged delays to surgery are a significant barrier within low-and-middle-income countries, leading to adverse outcomes for patients. Patients undergoing brain tumour surgery at public hospitals from lower or middle SES and electing for gross resections were more likely to have longer delays. Keywords: Treatment delay, Neuro-oncology, Time to surgery, Neurosurgery.